Immunopathology caused by impaired CD8+ T‐cell responses. Issue 9 (11th February 2022) - Aichele, Peter; Neumann‐Haefelin, Christoph; Ehl, Stephan; Thimme, Robert; Cathomen, Toni; Boerries, Melanie; Hofmann, Maike
Abstract: Recent findings indicate that many immunopathologies are at their roots a consequence of impaired immune responses ("too little" immunity) and not the result of primarily exaggerated immune responses ("too much" immunity). We have summarized this conceptional view as " IMPATH paradox ." In this review, we will focus on impaired immune reactions in the context of CD8 + T‐cell‐mediated immunopathologies. In particular, we will exemplify this concept in two disease models: Virus‐triggered primary hemophagocytic lymphohistiocytosis, an inflammatory syndrome caused by genetically impaired cytolytic functions of T cells, and viral hepatitis, where T‐cell exhaustion is a major underlying mechanism for impaired effector functions. In both situations, T cells fail to eliminate the source of immune stimulation, which usually serves as an important negative feedback loop curtailing immune reactions. Persistent antigen presentation by APCs and/or infected cells results in continuous stimulation causing chronic inflammation and immunopathology mediated by residual T‐cell functions. Hence, immune stimulation or reconstitution rather than immune suppression may be strategies for therapeutic interventions. Abstract : In virus‐triggered primary hemophagocytic lymphohistiocytosis and chronic viral hepatitis, impaired immune reactions may cause the underlying immune‐mediated pathology. In particular, dysfunctional CD8 + T cells fail to eliminate the main sources of immune stimulation (infected APCs/hepatocytes), in turn, fueling persisting inflammation and, thus, chronic immunopathology.